2020
DOI: 10.1002/rcm.8972
|View full text |Cite
|
Sign up to set email alerts
|

Rapid identification and discrimination of methicillin‐resistant Staphylococcus aureus strains via matrix‐assisted laser desorption/ionization time‐of‐flight mass spectrometry

Abstract: Rationale Methicillin‐resistant Staphylococcus aureus (MRSA) is one of major clinical pathogens responsible for both hospital‐ and community‐acquired infections worldwide. A delay in targeted antibiotic treatment contributes to longer hospitalization stay, higher costs, and increasing in‐hospital mortality. Matrix‐assisted laser desorption/ionization time‐of‐flight mass spectrometry (MALDI‐TOF MS) has been integrated into the routine workflow for microbial identification over the past decade, and it has also s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 40 publications
0
18
0
Order By: Relevance
“…Tang et al discovered nine characteristic peaks of MRSA among 214 S. aureus isolates ( 9 ). Liu et al discovered 38 characteristics peaks for a classification model from 452 clinical S. aureus isolates ( 10 ). Wang et al processed 4,858 mass spectra using various ML methods and identified 200 peaks as marker attributes for a predictive model.…”
Section: Introductionmentioning
confidence: 99%
“…Tang et al discovered nine characteristic peaks of MRSA among 214 S. aureus isolates ( 9 ). Liu et al discovered 38 characteristics peaks for a classification model from 452 clinical S. aureus isolates ( 10 ). Wang et al processed 4,858 mass spectra using various ML methods and identified 200 peaks as marker attributes for a predictive model.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies were mainly devoted to identifying methicillin-resistant Staphylococcus aureus (MRSA), and figuring out their informative peaks ( Wang et al, 2013 , 2020 ; Josten et al, 2014 ; Østergaard et al, 2015 ; Camoez et al, 2016 ; Rhoads et al, 2016 ; Bai et al, 2017 ; Sogawa et al, 2017 ; Kim et al, 2019 ; Tang et al, 2019 ; Liu et al, 2021 ). Bai et al (2017) proposed a genetic algorithm with a t -test based population seeding for wrapper feature selection on 727 Staphylococcus aureus clinical isolates’ mass spectra derived from Vitek MS, and their accuracy based on support vector machine classifier was 0.72.…”
Section: Discussionmentioning
confidence: 99%
“…Even though their prediction accuracy was over 90%, only 20 isolates were used. Liu et al (2021) used R to analyze 452 Staphylococcus aureus clinical isolates’ mass spectra derived from Vitek MS, and the best area under the receiver operating characteristic curve was 0.89 by support vector machine. Compared with previous studies, our study used much clinical data and considered three antibiotics.…”
Section: Discussionmentioning
confidence: 99%
“…The peak seems to be connected with the 50S ribosomal subunit and could be further investigated as a biomarker for MRSA [ 67 ]. Liu applied a machine learning approach (support vector machine algorithm) to identify peaks that could discriminate between MRSA and MSSA isolates They analyzed 194 MRSA and 258 MSSA and found 38 features that could discriminate MRSA from MSSA with a sensitivity of 84.0% and a specificity of 88.0% [ 68 ]. For an overview of studies on the identification of specific MRSA peaks, please refer to the works of Burckhardt and Liu [ 15 , 68 ].…”
Section: Phenotypic Methods For Antimicrobial Resistance Detection In S Aureusmentioning
confidence: 99%